Introduction to applied molecular biology - Cox, Jonathan (Henry Stewart Talks, 2021)
Molecular biology, Polymerase chain reaction and the enzymes that make cloning possible, Examples of applied molecular biology techniques in health and disease, Cloning in bacteria, yeast and eukaryotes, GMOs and regulation